The Impact of Policy and Resources on Public Service Performance: The Mediating Role of Implementer Attitude (A Study at Gapura Surya Nusantara Passenger Terminal) - Sapit Hidayat; Siswo Hadi Sumantri; Sri Umiyati; Sudirman Sudirman (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the influence of policy and resources on public service performance through the mediating role of implementer attitude at the Gapura Surya Nusantara Passenger Terminal, Tanjung Perak Port, Surabaya. The research adopts a quantitative explanatory approach by integrating policy implementation theory and organizational resource perspectives to explain service performance dynamics within the maritime transportation sector. Data were collected from 400 passengers using structured questionnaires and analyzed through Partial Least Squares Structural Equation Modeling. The findings demonstrate that policy, resources, and implementer attitude satisfy the required standards of reliability and validity, confirming the robustness of the measurement model. Structural analysis reveals that policy and resources exert significant positive effects on both implementer attitude and public service performance. Implementer attitude also has a significant positive effect on performance outcomes. Mediation testing confirms that implementer attitude partially mediates the relationships between policy and performance as well as between resources and performance. The study highlights the importance of combining institutional arrangements with behavioral factors to improve service quality. These findings contribute to public administration literature by providing empirical evidence from the maritime public service context and offer practical implications for strengthening passenger service management.